The role of autophagy in squamous cell carcinoma of the head and neck. (March 2016) - Cosway, Benjamin; Lovat, Penny
Abstract : Highlights: Early trials suggest autophagy may be an exciting treatment target for cancer. Biomarkers of autophagy status are prognostic in head and neck cancer. Autophagy can be modulated in vitro to promote cell death in this disease. Autophagy is intimately linked to key pathways in head and neck cancer. In future, bespoke treatment strategies based on autophagy status may be possible. Summary: Half a million new head and neck cancers are diagnosed each year worldwide. Although traditionally thought to be triggered by alcohol and smoking abuse, there is a growing subset of oropharyngeal cancers driven by the oncogenic human papilloma virus (HPV). Despite advances in both surgical and non-surgical treatment strategies, survival rates have remained relatively static emphasising the need for novel therapeutic approaches. Autophagy, the principal catabolic process for the lysosomal – mediated breakdown of cellular products is a hot topic in cancer medicine. Increasing evidence points towards the prognostic significance of autophagy biomarkers in solid tumours as well as strategies through which to harness autophagy modulation to promote tumour cell death. However, the role of autophagy in head and neck cancers is less well defined. In the present review, we summarise the current understanding of autophagy in head and neck cancers, revealing key areas for future translational research.